The effects of a non-woven cover in combination with different soil mulches in strawberry cultivation - A. AFLATUNI; R. KEMPPAINEN; A. HEINONEN (Scientific Agricultural Society of Finland, 2008)
The effects of a non-woven cover and three different soil mulches on the timing of harvest and on the yield of strawberry were examined in two field experiments in northern Finland during 1989-1993. The non-woven cover was used either in spring or in both autumn and in spring. Non-covered plants served as controls. Depending on the year, plants covered in spring alone gave a significantly earlier (4 to 9 days) marketable yield than did uncovered plants. The non-woven cover had no effect on marketable yield at Sotkamo but at Rovaniemi it increased the yield, especially in cold years. The use of cover decreased the amount of mouldy berries. At both experimental sites, a significantly higher yield was obtained from beds covered with soil mulches than from uncovered beds. White-on-black film delayed the yield by 2 to 4 days in comparison with black or Mypex film.